Exhaled Breath Volatile Organic Compounds in Pregnancy: A Pilot Study - Farghaly, Mohsen A.A.; Abuelazm, Somaya; Farrell, Ruth M.; Elgendy, Marwa M.; Grove, David; Abu-shaweesh, Jalal M.; Dweik, Raed A.; Aly, Hany (American Journal of Perinatology, 2024)
This study aimed to assess the volatile organic compounds (VOC)s in breath samples collected noninvasively from pregnant women during pregnancy and postpartum and compare it with nonpregnant controls.This pilot study included 50 subjects: 10 pregnant patients in their first trimester, 10 in second trimester, 10 in third trimester, 10 in the first postpartum week, and 10 nonpregnant subjects as a control. We collected exhaled breath from subjects who reported to be healthy and free of any respiratory symptoms. Clinical and demographic data were collected. The samples were analyzed for VOCs using a selected-ion flow-tube mass spectrometer.The VOCs monitored were 22 compounds selected for their common presence in exhaled breath. During pregnancy and postpartum period, there were differences in five compounds mainly: 2-propanol, acrylonitrile, 1-nonene, 2-nonene, and hydrogen sulfide. Significant differences in VOCs were identified during each trimester compared with controls.VOCs could be measured safely and noninvasively in pregnant women. VOCs differed significantly among nonpregnant, pregnant women, and postpartum period. The utilization of this novel assay to identify fetal conditions or identifying women at risk of premature delivery, which should be further investigated in future studies.
Keywords: fetal; maternal; preterm; neonate; pregnant; metabolomics; VOCs